Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan (Studi pada Karyawan di Perpustakaan Universitas Brawijaya Malang) - Khairizah, Astria (Jurnal Administrasi Publik, 2015)
Abstract: The Effects of Leadership Style on Employee’s Performance (Studies on Employees in the Library of Brawijaya University Malang). Library is organization or institution which oriented in information. In the library organization hierarchy between the leader and the subordinates is necessary. The leadership style used by the leader in the library can influence the employee’s performance to cooperate and to reach the goal of the library. This research uses survey method. The population in this research is 65 people and the sample which has been decided is 55 people, who are permanent employess at the Library of Brawijaya University Malang. The data resources used primary data that obtained by distributing questionnaires, interviews, and documentation, which tested by IBM Statistics 21 for Windows. Simultantly, the result said that directive; supportive; and participative influencing the employee’s performance. Directive partially have influence on the employee’s performance, but supportive and, participative not influencing the employee’s performance in the UB’s Library. Keyword: directive leadership style; supportive leadership style; participative leadership style; employee’s performance Abstrak: Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan (Studi pada Karyawan di Perpustakaan Universitas Brawijaya Malang). Perpustakaan sebagai lembaga informasi membutuhkan struktur antara pimpinan dan bawahan. Di perpustakaan, pimpinan dengan gayanya bisa mempengaruhi kinerja karyawannya agar melaksanakan tugas. 65 orang sebagai populasi dengan sampel yang telah ditentukan sebanyak 55 orang yang merupakan karyawan tetap di Perpustakaan Universitas Brawijaya Malang. Sumber data yang digunakan adalah data primer yang diperoleh dari penyebaran kuisioner, wawancara, dan dokumentasi yang diuji dengan IBM Statistics 21 for Windows. Secara bersama-sama semua variabel (X) mempunyai pengaruh pada kinerja karyawan. Pemimpin yang direktif memiliki pengaruh secara sendiri-sendiri pada kinerja karyawan, sedangkan pemimpin suportif dan partisipatif tidak mempengaruhi kinerja karyawan di Perpustakaan UB.   Kata Kunci: gaya kepemimpinan direktif; gaya kepemimpinan suportif; gaya kepemimpinan partisipatif;  kinerja karyawan